Analysis of Online Customer Reviews Toward Interest Using Blibli as Online Marketplace in UPI Students - Hidayat, Rachmat; Dahlan, Dadang (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: This study aims to analyze and determinate the influence of online customer reviews toward using online marketplace. Methodology: The research method is used in an explanatory survey with hypothesis testing with data collection technique employed through questionnaires. The study population are student from indramayu who studied in Univeristas Pendidikan Indonesia 2019 were 135 as respondents. The collected data were then analyzed using simple regression techniques. Results: The results showed that the online customer reviews variable were categorized as significant and interest of using with a coefficient of 0.691 Applications/Originality/Value: This finding implies that to improve e-commerce, so companies need to more attention to how they can prioritize consumer desires so that good online reviews for the company will be achieved.